Desenvolvimento de biossensor enzimático baseado em esterases obtidas de bactéria endofítica para determinação do pesticida metomil - Jantsch, Márcia Regina (2017)
In this work, a biosensor based on the adsorption of esterase enzymes produced by endophytic bacteria Microbacterium paraoxydans strain in nanoargila was developed using a paste based on graphite and carbon nanotubes (CNT) for the determination of methomyl pesticide. The application of enzymes from endophytic bacteria in the construction of the biosensor is unprecedented, making the research innovative. Carbamate class pesticides have a reversible action on the inhibition of esterase enzymes, this inhibition can be used as an analytical response for the detection of the methomyl insecticide/miticide. Previously, 47 bacteria collected in Sandy Hook, New Jersey USA, were evaluated for the production potential of esterase enzymes, and two of these were preselected to optimize the pH and culture time. The bacterial source selected was the one with the highest enzymatic activity, with 5.58 U mL-1 on the third day of culture in liquid medium based on Tween 20, CaCl2, peptone and alkaline pH. For the construction of the biosensor, 0.3 units of enzyme were immobilized on montmorillonite support modified with ammonium salts and after incorporated with graphite / CNT / support / Nujol an proportion 53.0 / 5.9 / 11.8 / 29.3% (m / m), respectively. The biosensor response was optimized for the p-NPA substrate in 0.1 mol L-1 saline phosphate buffer (0.1 mol L -1 NaCl pH 7.0) by square wave voltammetry (SWV), with frequency of 70 Hz, scanning increment of 2.0 mV, pulse amplitude of 100.0 mV and potential of conditioning of -0.4 mV for 150 seconds. The biosensor showed good repeatability (N = 10) with RSD 4.77% and intermediate precision (N = 5) with RSD 4.04%, remaining stable for a period of 9 weeks. The linear range of biosensor response is between 10 and 100 ug L -1 (r = 0.9929) with detection and instrument quantification limits of 3.47 and 10.53 ug L -1 , respectively. The mean recovery of methomyl in surface water sample ranged from 99.29 to 104.72%, for levels of fortification of 10, 50 and 75 ug L -1 , indicating good accuracy in the biosensor response. The biosensor did not present a significant difference when compared with the chromatographic method (UHPLC), at a confidence level of 95%, demonstrating the applicability of the biosensor to the determination of the methomyl pesticide in surface water.